2014
DOI: 10.1007/s11250-014-0556-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sheep grazing in pastures of Brachiaria decumbens, Brachiaria brizantha, Panicum maximum, and Andropogon gayanus with different protodioscin concentrations

Abstract: Brachiaria spp. are the most important grasses for ruminants in central-western Brazil. However, the use of these pastures is limited by their toxicity due to steroidal saponins. This experiment was conducted for 60 days to demonstrate the resistance of sheep raised on Brachiaria spp. pastures to steroidal saponin poisoning. The experiment was composed by 48 animals randomly divided into four groups (n = 12). Among them, 32 4- to 5-month-old castrated male crossbred Santa Inês sheep, originating from flocks th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
21

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 10 publications
3
27
0
21
Order By: Relevance
“…The animals recovered 30 and 40 days after initiating the treatment strategy, which agrees with Gracindo et al (6) who reported that recovery time of the affected cattle was between 15 and 45 days after being removed from the areas with Brachiaria spp. ; however, it states that it is likely that the animals have cutaneous scars until slaughter.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The animals recovered 30 and 40 days after initiating the treatment strategy, which agrees with Gracindo et al (6) who reported that recovery time of the affected cattle was between 15 and 45 days after being removed from the areas with Brachiaria spp. ; however, it states that it is likely that the animals have cutaneous scars until slaughter.…”
Section: Discussionsupporting
confidence: 88%
“…located in canaliculi, bile ducts, and to a lesser extent in hepatocytes and is released when there these structures are damaged. Similarly, Gracindo et al (6) and Faccin et al (14) reported in their study that the mean serum catalytic activity of GGT in sheep that grazed on B. decumbens was higher than sheep that grazed in paddocks with other grass.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations